Roles & mechanisms of NANOG-mediated drug resistance in human colorectal cells - Shaheen, Sameerah (2017)
NANOG is a transcription factor that functions as a central regulator of pluripotency and determines the cell fate in embryonic stem cells (ESCs). Dr Nateri’s laboratory and others have reported the expression of embryonic NANOG in a small subpopulation of cells in several human cancers including human colorectal cancer (CRC). NANOG positive CRC cells express the normal intestinal stem cell marker LGR5, as well as the induced pluripotent stem (iPS)-linked transcription factors SOX2, c-MYC, and high β-catenin. These cells strongly resemble a small subpopulation of poorly differentiated cancer stem cells (CSCs). Recent studies have reported that, in CSCs, the self-renewal and survival signals are dominant over the differentiation signals. This suggests that NANOG is an essential modulator of drug resistance complexity and tumour heterogeneity in cancer cells.